The increasing hub pricing and market integration in EuropeThe increasing hub pricing and market integration in Europe - Petrovich, B (Oxford Institute for Energy Studies, 2015)
Since 2007, the sale and purchase of natural gas in Europe has been evolving from a ‘traditional’ model based on bilateral long-term contracts with prices (largely) linked to those of oil products, to trading by means of standardized contracts concluded between a large number of participants with prices set by supply and demand ‘at the hub’.